Beginning Android 3D Game Development - Chin, Robert (Apress, 2014)
Beginning Android 3D Game Development is a unique, examples-driven book for today's Android and game app developers who want to learn how to build 3D game apps that run on the latest Android 5.0 (KitKat) platform using Java and OpenGL ES. Android game app development continues to be one of the hottest areas where indies and existing game app developers seem to be most active.  Android is the second best mobile apps eco and arguably even a hotter game apps eco than iOS.  3D makes your games come alive; so in this book you'll find that we go in depth on creating 3D games for the Android platform with OpenGL ES 2.0 using an original case study game called Drone Grid. Moreover, this book offers an extensive case study with code that will be modular and re-useable helping you create your own games using advanced vertex and fragment shaders.  Drone Grid is a game app case study that is somewhat similar to the best selling Geometry Wars game series utilizing a gravity grid and colorful abstract graphics and particles. After reading and using this book, you'll be able to build your first 3D Android game app for smartphones and tablets.  You may even be able to upload and sell from popular Android app stores like Google Play and Amazon Appstore.